The economic potential of the brics countries as a challenge to modern world realities - Streltsov, Evgeny Sergeevich (2021)
Today, the governments of various countries, regardless of the level of economic growth of the state, strive to initiate macroeconomic policies aimed at achieving better economic indicators in order to increase the level of business activity and, finally, to ensure a better quality of life for people. In this regard, the policy of the BRICS countries is very indicative. The author analyzes the importance of the BRICS group as representatives of developing countries in the world economy. The article points out that the financial crisis did not have a strong impact on the BRICS group, and its economic performance was much better than that of developed countries. The main factors that led to the economic expansion of the group were the increased influence in a number of markets, as well as the huge scale of resources, including labor. For example, Brazil and Russia rely mainly on huge mineral reserves and speculation in international markets. China has the advantage of cheap labor and resources at low prices. India also relies on cheap labor. Last but not least, all the BRICS countries, except Brazil, demonstrate very high rates of investment. The purpose of the work is to consider the economic potential of the BRICS countries as a challenge to modern economic realities.